2016
DOI: 10.15406/aovs.2016.05.00142
|View full text |Cite
|
Sign up to set email alerts
|

Normal Values of Corneal Optical Densitometry Using Pentacam Scheimpflug Camera

Abstract: Purpose: The purpose of the study was to illustrate the range of normal values of corneal densitometry using Pentacam Scheimpflug camera. Methodology:Prospective study was conducted at tertiary care Amanat eye hospital. 490 eyes of 490 participants of different age groups were added. All scans were performed in diagnostics room with uniform ambient light, performed by trained ophthalmic technologist. All participants were Pakistani of different ethnic groups. Only one eye of each participant was included to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…In our study, corneal densitometry, in the examined central 0- to 2-mm zone, was found to be significantly positively correlated with age, both at each layer separately (anterior, central, and posterior) and in total. These results come in accordance with those of Asrar et al 18 who found significant correlation between age and corneal densitometry in every annular concentric zone and corneal layer. The increase in densitometry over aging might reflect the age-related changes that take place in all corneal layers, such as disruption of the epithelial cell barrier function, reduction of keratocyte density, breakdown of collagen fibers and appearance of collagen-free spaces, dysgenic or apoptotic cellular remnants in the aged stroma, such as lipofuscin granules (corneal farinata), and reduction of endothelial CD.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, corneal densitometry, in the examined central 0- to 2-mm zone, was found to be significantly positively correlated with age, both at each layer separately (anterior, central, and posterior) and in total. These results come in accordance with those of Asrar et al 18 who found significant correlation between age and corneal densitometry in every annular concentric zone and corneal layer. The increase in densitometry over aging might reflect the age-related changes that take place in all corneal layers, such as disruption of the epithelial cell barrier function, reduction of keratocyte density, breakdown of collagen fibers and appearance of collagen-free spaces, dysgenic or apoptotic cellular remnants in the aged stroma, such as lipofuscin granules (corneal farinata), and reduction of endothelial CD.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, age-related alterations in the endothelial layer could contribute to the observed increase in CD values. Consistent with the study conducted by Asrar and Ni Dhubhghaill et al [2,17], our ndings indicated a strong association between peripheral corneal backscatter and age. This correlation may be attributed to the development of age-related limbal deformations, including the farinata, Arcus senilus/lipoides, crocodile shagreen, Vog''s white limbal girdle, and Hassal-Henle bodies.…”
Section: Resultssupporting
confidence: 93%
“… 30 Moreover, different studies have shown a range of 4–19 with a mean of 12 for densitometries in the normal corneas, and the anterior layer has always had the most density with a mean of about 19. 21 31 32 It could be mentioned that peripheral corneal densitometry values remarkably increase with aging. It seems that corneal densitometry can be an indicator for endothelial cell properties.…”
Section: Discussionmentioning
confidence: 99%